Morphological characteristics of multiple cysts of the jaws in children - Kyseliova, Н. В. (Actual Dentistry, 2024)
Purpose. This study aimed to analyze the morphological structure of multiple cysts of the jaws in children. Methods. A retrospective analysis was conducted on 240 case histories of patients with cystic lesions of the jaws over 4 years. Nine children were found to have multiple cystic lesions in their jaws. Fourteen orthopantomograms and six CT scans, and 42 histological preparations, were analyzed. Results. Four percent of patients with cystic neoplasms had multiple cystic lesions in their jaws. The average age of the patients was 12.22 ± 1.07 years. Polycystic jaws were accompanied to a greater extent by damage to the lower jaw in 64% (p = 0.017), in particular the areas of the corner, second and third molars in 33%. Three types of cystic neoplasms were identified after reviewing 42 histological biopsies: simple bone cyst (n = 5) in 33% of patients, dentigerous cyst (n = 15) in 88% of children, and odontogenic keratocyst (n = 22) in 100%. Conclusions. Multiple cystic lesions of the jaws are associated with syndromes. Polycystic lesions of the jaws involve both the upper and lower jaws and consist of cysts of both odontogenic and non odontogenic origin. Odontogenic keratocysts are the most common cystic lesions. These are characterized by: the presence of satellite cysts; a developed basement membrane, with pronounced keratinization and parakeratosis; and more than 10 densely cellular layers of parakeratinized squamous epithelium.